2015
DOI: 10.14814/phy2.12323
|View full text |Cite
|
Sign up to set email alerts
|

Precision-cut rat, mouse, and human intestinal slices as novel models for the early-onset of intestinal fibrosis

Abstract: Intestinal fibrosis (IF) is a major complication of inflammatory bowel disease. IF research is limited by the lack of relevant in vitro and in vivo models. We evaluated precision-cut intestinal slices (PCIS) prepared from human, rat, and mouse intestine as ex vivo models mimicking the early-onset of (human) IF. Precision-cut intestinal slices prepared from human (h), rat (r), and mouse (m) jejunum, were incubated up to 72 h, the viability of PCIS was assessed by ATP content and morphology, and the gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(60 reference statements)
2
20
0
Order By: Relevance
“…Recently, the application of PCTS was further extended to study the mechanism of fibrosis, which is characterized by the excess deposition of extracellular matrix. It has been shown that PCTS from different organs develop inflammatory and fibrogenic responses during culture, making PCTS a suitable model for fibrosis and analysing the effect of antifibrotic compounds (Kasper et al 2004;Westra et al 2014Westra et al , 2016Pham et al 2015;Stribos et al 2016;Alsafadi et al 2017;Luangmonkong et al 2017Luangmonkong et al , 2018. Furthermore, PCTS generated from human diseased organs allow the investigation of fibrosis in situ, as we previously showed for human cirrhotic liver PCTS (Luangmonkong et al 2017).…”
Section: Introductionmentioning
confidence: 70%
“…Recently, the application of PCTS was further extended to study the mechanism of fibrosis, which is characterized by the excess deposition of extracellular matrix. It has been shown that PCTS from different organs develop inflammatory and fibrogenic responses during culture, making PCTS a suitable model for fibrosis and analysing the effect of antifibrotic compounds (Kasper et al 2004;Westra et al 2014Westra et al , 2016Pham et al 2015;Stribos et al 2016;Alsafadi et al 2017;Luangmonkong et al 2017Luangmonkong et al , 2018. Furthermore, PCTS generated from human diseased organs allow the investigation of fibrosis in situ, as we previously showed for human cirrhotic liver PCTS (Luangmonkong et al 2017).…”
Section: Introductionmentioning
confidence: 70%
“…8 However, most of these models use healthy tissues from rats or mice and stimulate them with TGF-β1 to induce a fibrogenic response. [15][16][17] In a recent study, the use of PCTS from human kidneys has been proposed to study the mechanisms of fibrosis. 18 However also in this experimental approach, fibrosis is induced in already cultured slices by means of TGF-β stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…These slices are produced to stay vital in culture and have been already used to study the intestinal tissue in smaller species like rodents (Niu et al, 2014). So far they have been established in rat, mouse, and human jejunum (Pham et al, 2015). Here for the first time, we established porcine jejunum PCIS and demonstrate that they can be infected by different TGEV strains.…”
Section: Introductionmentioning
confidence: 95%